Multiple facets of p53 in senescence induction and maintenance - Johmura, Yoshikazu (Cancer Sci, 2016)
Cellular senescence is a state of durable cell cycle arrest with metabolic activities distinct from those of the proliferative state. Since senescence was originally reported to be induced by various genotoxic stressors, such as telomere erosion and oncogenic signaling, it has been proposed to play a pivotal role in aging‐related changes and as an antitumorigenic barrier in vivo. However, the mechanisms underlying its induction and maintenance remain entirely elusive. We have recently found that abrupt activation of p53 at G(2) results in a cell skipping mitosis and subsequently undergoing senescence. Surprisingly, we have also found that downregulation of p53 by SCF(F) (bxo22) is crucial for the induction of a senescence‐associated phenotype. In this review, we provide an overview of recent advances in understanding the mechanisms underlying the timing and magnitude of activation of p53 during senescence.